The university student's knowledge of the effect of lines on Clothes on the body and shape of the body (Journal of the College of Basic Education, 2022)
Wearing appropriate clothing grant respect for oneself, respect of othersand promote a sense of self-confidence.Many factors intervene in the selection of appropriate clothing such aspersonality, and the event being attended , shape and body figure.Appearance depend on clothes more than the body shape , the body may seemsmaller or larger than what it really seen ,by using the design elements, color ,shape , line and texture of the clothes .